ASSOCIATION OF AGE AND FOUR SCORE WITH ICU LENGTH OF STAY IN POST-CRANIOTOMY PATIENTS AT SAKINAH HOSPITAL MOJOKERTO - Rudi Hariyono; Ika Ainur Rofi’ah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
This study aimed to analyze the association factors between age, FOUR Score, and ICU length of stay among post-craniotomy patients treated at Sakinah Hospital. A cross-sectional study was conducted from 01 October to 12 December 2025 involving adult post-craniotomy patients admitted consecutively to the ICU. Eligible participants were ≥18 years old, intubated postoperatively, and had a completed FOUR Score assessment. Fisher’s Exact Test and relative risk (RR) with 95% confidence intervals (CI) were applied to examine associations between age, FOUR Score, and ICU LOS. A significance level of p < 0.05 was used. 29 patients, 58.6% were aged ≥53 years and 62.1% experienced prolonged ICU stay. A FOUR Score ≤10 was observed in 58.6% of the cohort. Lower FOUR Scores were strongly associated with prolonged ICU stay (p < 0.000; RR = 9.7; 95% CI: 1.4–63.8). Older age also demonstrated a significant association with extended LOS (p = 0.018; RR = 2.47; 95% CI: 1–7.7). Both advanced age and lower FOUR Scores were significant associated with prolonged ICU stay among post-craniotomy patients. These findings underscore the utility of integrating neurological scoring with demographic risk profiling to support early prognostication and guide resource allocation in neurosurgical critical care.